2009
DOI: 10.1093/cvr/cvp151
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and pharmacology of the mitochondrial permeability transition pore

Abstract: The 'mitochondrial permeability transition', characterized by a sudden induced change of the inner mitochondrial membrane permeability for water as well as for small substances ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
180
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(194 citation statements)
references
References 141 publications
(177 reference statements)
5
180
0
3
Order By: Relevance
“…It is at least prudent to consider that the composition and/or regulation of the mitochondrial PTP exhibits tissue-or even cell-specific differences, as it has been suggested elsewhere (44,45). …”
Section: Discussionmentioning
confidence: 99%
“…It is at least prudent to consider that the composition and/or regulation of the mitochondrial PTP exhibits tissue-or even cell-specific differences, as it has been suggested elsewhere (44,45). …”
Section: Discussionmentioning
confidence: 99%
“…It is clear that mitochondrial permeability transition (MPT) pore formation is characterized by the loss of mitochondrial transmembrane potential (MTP) and plays a key role in determining whether the cell lives or dies (Zorov et al, 2009). However, in terpinen-4-ol-treated HL-60 cells, cytochrome c release was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies with mitochondria from knockout mice have suggested that Cyp-D has more of a regulatory role in mPTP opening. In contrast, VDAC appears dispensable for pore formation, and at this time there is no compelling evidence that VDAC serves a regulatory role either [27].…”
Section: Mitochondrial Permeability Transition Porementioning
confidence: 92%